Aspartic Acid- and Glycine-Functionalized Mesoporous Silica as an Effective Adsorbent to Remove Methylene Blue from Contaminated Water - Abdullah M. Alswieleh (Journal of Chemistry)
In this work, aspartic acid- and glycine-functionalized mesoporous silica nanoparticles (Asp-MSNs and Gly-MSNs) were successfully prepared and applied as adsorbents for removal of methylene blue (MB) from contaminated water. The mesoporous structure of the fabricated nanomaterials was confirmed by nitrogen adsorption/desorption with specific surface area of ca. 700 m2/g and pore volume of 0.9 cm3/g for both Asp-MSNs and Gly-MSNs. The average size of the nanoadsorbents was estimated to be ca. 290 nm as characterized by scanning electron microscopy (SEM) and transmission electron microscope (TEM). The physical and chemical properties of the Asp-MSNs and Gly-MSNs were also characterized by Fourier transform infrared (FTIR) spectroscopy, zeta potential, and elemental analysis. Asp-MSNs and Gly-MSNs exhibited good adsorption performance for removal of cationic organic dyes (MB). The equilibrium adsorption capacity of Asp-MSNs and Gly-MSNs was found to be 55 mg·g−1 and 43 mg·g−1, respectively, under the optimal conditions. The Langmuir model and pseudo-second-order equation exhibited good correlation with the isotherm and adsorption kinetic data for MB, respectively.